Elemen Pembentuk Karakter Rumah 1870 di Kampung Heritage, Kayutangan Kota Malang - Afifah Khairunnisa; Antariksa Sudikno (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2022)
The house has character elements that show the style applied in the house. The character of the house can be seen in the architectural character, from the spatial and visual character. The elements composing the character of the house consist of floor plans, interiors, and facades. Beyond time, there was a change in the character of the house due to architectural developments and the needs of the residents of the house. However, there is the oldest house with the Dutch East Indies architectural style that stands till today, namely Rumah 1870 which is located in the Kayutangan Heritage Village. The purpose of this study was to determine the architectural character of Rumah in 1870. The method used was the descriptive analysis method, to obtain and analyze the data of the existing condition. The results of the study show that the architectural character of Rumah 1870 still shows the architectural style of the Dutch East Indies, although there have been changes or additions to the character of the house.